I24 MHC matching fails to prevent long-term rejection of ipsc-derived neurons in non-human primate. (September 2018) - Badin, Romina Aron; Bugi, Aurore; Williams, Susannah; Vadori, Marta; Michael, Marie; Jan, Caroline; Nassi, Alberto; Lecourtois, Sophie; Cozzi, Emanuele; Hantraye, Philippe; Perrier, Anselme L
Abstract : Securing scalable sources of cell therapy products with enhanced or full immunological compatibility could be achieved by matching haplotypes of iPSC donors (HLA homozygous lines). Recent experiments have shown that major histocompatibility complex (MHC) matching could be a solution for allogeneic stem cell transplantation in the retina#1 and in the striatum#2 of non-lesioned non-human primates (NHP) without immunosuppressive medication for 6 and 4 months post-transplantation, respectively. Here we present a study in which we challenged the efficacy of MHC matching in long-term allograft rejection in a NHP model of Huntington's disease. We performed a comparative assessment of the immunogenicity of autologous, haplotype-matched and two-haplotype mismatched neuronal grafts in the excitotoxically-lesioned striatum of NHP. First, blood cells from different NHPs homozygous for MHC Class I&II were used to produce several iPSC lines that were subsequently differentiated into striatal cells. Next we assessed their potential immunogenicity at 3 and/or 6 months after intra-striatal grafting in haplotype mis-matched, matched and autologous NHP recipients. Our results suggest that, unlike autologous neuronal grafts, allogenic and haplotype-matched grafts elicit a local infiltration of CD8+ T cells, CD68+ macrophages cells and an increase in local Iba1 and HLA-DR staining. Serum levels of antibodies against all 3 types of grafted cells and their ability to trigger complement dependent cytotoxicity (CDC) in vitro were measured longitudinally and no humoral response or CDC activity were elicited by the graft at any time after transplantation. In the specific context of transplantation in the brain, our pre-clinical data suggest that, HLA matching alone is insufficient to grant long-term graft survival but could be a cost effective compromise to reduce peripheral immunosuppression and its side effects in the clinical setting.